Medicinal Plants used by Koch Rajbangshi of North Salmara Subdivision, Bongaigaon, Assam, India - Das, Ashoke Kumar; Choudhury, Manabendra Ray; Sharma, Gajen Chandra (Our Nature, 2013)
A total of 73 medicinal plants belonging to 44 families of angiosperms were found to be used in the healing practice of 36 types of diseases including diabetics, heart problem, and neurological disorders by Koch Rajbangshi people of North Salmara sub-division of Bongaigaon district, Assam. More use of leaf was found in disease treatment than other parts of plant. Among the plants species 49 were common in occurrence, 19 species less common and 5 species viz., Aristolochia indica L., Asparagus recemosus Willd., Cissus quadrangularis L., Garcinia morella (Gaertn.) Desv and Rauvolfia serpentina Benth. were in rare category in the study area. DOI: http://dx.doi.org/10.3126/on.v11i1.8243 Our Nature Vol.11(1) 2013: 45-53